Innovative entrepreneurship and quality of life. The case of Ecuador. Issue 1 (17th November 2020) - Aguirre, Juan Carlos; Peralta Zuñiga, Marco Leonardo; Mora, Pedro; Blanco, Francisco
Abstract : Purpose: This article is based on the assumption that entrepreneurship improves quality of life (HDI). Its main objective is to establish causal relationships between entrepreneurship variables such as credits, innovation (R&D), business growth, foreign direct investment and the Global Competitiveness Index and how these have influenced a country's development. Design/methodology/approach: To analyse and validate this assumption, relevant information has been extracted about Ecuador (the subject of the study) for the 1998–2017 period. The information has received the respective econometric treatment, through a multivariate estimation by the autoregressive vector (ARV) method that made it possible to establish impulse-response functions. Results: The results indicate that there is a significant and positive statistical impact between the variables related to entrepreneurship and quality of life (HDI), with the exception of "Innovation", which is not representative in the model, demonstrating that the investment made at country level in R&D is not sufficient to have an impact on the HDI. It was also determined that promoting entrepreneurship would be useful as this would alter the trend of the variables, making them conducive to increasing the HDI. Originality/value: This article is one of the few to address this issue. It includes the self-regressive vector model as a key methodology used to evaluate and establish public policies. RVM has provided positive results in the field of economics and can be adopted in the area of entrepreneurship. Abstract : Propósito: El presente artículo se basa en el supuesto de que el emprendimiento mejora la calidad de vida de los individuos (IDH), siendo el objetivo principal establecer relaciones causales entre variables de emprendimiento como: Créditos, Innovación (I + D), Crecimiento Empresarial, Inversión Extranjera Directa e Índice de Competitividad Global; y, como estas han influido en el desarrollo de un país. Diseño/metodología/enfoque: Para el análisis y validación del supuesto mencionado anteriormente, se ha extraído información relevante sobre el Ecuador (sujeto de estudio) para el período comprendido entre 1998 y 2017, a los cuales se les ha dado el respectivo tratamiento econométrico, a través de una estimación multivariante por el método de Vectores Autorregresivos (VAR) que permitió establecer funciones de impulso – respuesta. Resultados: Los resultados señalan que existe una significativa incidencia estadística entre las variables relacionadas con el emprendimiento y la calidad de vida (IDH) de manera positiva, a excepción de la "Innovación" que no tiene representatividad en el modelo, demostrando que la inversión realizada a nivel país en I + D es insuficiente para impactar el IDH. También se determinó la conveniencia de impulsar el emprendimiento, pues esto cambia la tendencia de las variables haciéndolas favorables para el crecimiento del IDH. Originalidad/valor: Este artículo es uno de los pocos en abordar esta problemática, además incluye el Modelo de Vectores Autorregresivos como una metodología clave para evaluar y establecer políticas públicas, que ha brindado resultados positivos en el campo de la Economía y que puede adoptarse en la rama del Emprendimiento.